Member

JP2025036317APending Publication Date: 2025-03-14TOTO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024147016
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-31
Filing Date
2024-08-28
Publication Date
2025-03-14

AI Technical Summary

Benefits of technology

【0010】 本発明によれば、水と、有機成分および無機成分を含む汚染物質とが表面に付着し、且つ表面に水と汚染物質とが混在した状態で水が乾燥するというサイクルが繰り返される環境下において、表面への汚れ、とりわけ水垢およびタンパク質の付着または固着を抑制することができ、さらに付着した汚れを容易に、すなわち小さい清掃負荷で除去することができる部材が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025036317000001_ABST
    Figure 2025036317000001_ABST
Patent Text Reader

Abstract

To provide a member that can suppress adhesion of contaminants such as water scale and proteins.SOLUTION: The present invention provides a member for use in an environment involving repeated cycles in which water and contaminants containing organic and inorganic components adhere to the surface, and water dries while the water and the contaminants are mixed on the surface, wherein the member comprises a substrate and a surface layer, and the surface layer comprises a specific betaine structure and a specific structure having hydrophilic and anionic properties.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a member, specifically to a member intended to be used in an environment in which water and contaminants containing organic and inorganic components adhere to a surface, and the water dries while the water and contaminants are still mixed on the surface, resulting in a repeated cycle. [Background technology]

[0002] When tap water adheres to the surface of a component used in an environment where it may be exposed to water and dries, the inorganic components contained in the tap water adhere to the surface and form limescale. A typical inorganic component is silicate ions (SiO3 2- ) and calcium ions (Ca 2+ ) Silicate ion (SiO3 2- ) are polymerized by dehydration condensation, and calcium ions react with CO2 in the air or water, densely crystallizing as calcium carbonate as the water evaporates, and these adhere to the surface of the component, either alone or as a mixture, to form limescale. When a large amount of water adheres to the surface of the component, or when water is repeatedly applied to and dried on the surface of the component, the amount and frequency of silicate ions and calcium ions adhering to the surface of the component increases, accelerating the formation of limescale and resulting in a state in which limescale adheres strongly to the surface of the component, i.e., the limescale is fixed to the surface of the component.

[0003] In addition to water, various contaminants such as the inorganic components (silicate ions, calcium ions, etc.) and organic components (sebum, soap scum, rinse, proteins, etc.) mentioned above adhere to the surface of the component. These contaminants remain on the surface of the component when the water dries. In many cases, at least one or more types of these contaminants adhere to the surface of the component, and a mixture of water stains and contaminants is formed on the surface of the component after drying. Technologies for modifying the surface of the component have been proposed to suppress the adhesion of such contaminants and to improve the cleanability of adhered contaminants.

[0004] For example, JP 2008-239949 A (Patent Document 1) discloses a hydrophilic member having a surface excellent in antifouling properties, antifogging properties and abrasion resistance. Specifically, the member discloses a hydrophilic film formed on a substrate by bonding a zwitterionic low molecular weight compound having a betaine structure to a hydrophilic polymer having a silane coupling group at the end or side chain by silane coupling, and introducing inorganic components such as Si, Ti, Zr, and Al for densification.

[0005] In addition, WO2018 / 079592 (Patent Document 2) discloses a laminate sheet having a substrate layer and a hydrophilic coating layer formed using a resin composition containing an aqueous polyester resin and a zwitterionic polymer. This laminate sheet is said to be resistant to fogging and has excellent antifouling properties.

[0006] In addition, WO2018 / 155577 (Patent Document 3) discloses a hydrophilic structure having a layer structure in which a substrate, an intermediate layer, and a hydrophilic layer are laminated in this order, the intermediate layer being a layer containing a siloxane-based polymer, and the hydrophilic layer containing a zwitterionic polymer having no silicon atoms. This structure is said to have excellent hydrophilicity, stain resistance, adhesion, and water resistance. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2008-239949 A [Patent Document 2] WO2018 / 079592 publication [Patent Document 3] WO2018 / 155577 publication Summary of the Invention [Problem to be solved by the invention]

[0008] The present inventors have focused on the fact that proteins are present at a high ratio among various contaminants present on the surface of components used in an environment where water and contaminants containing organic and inorganic components adhere to the surface, and the water dries while the water and contaminants are mixed on the surface, and this cycle is repeated. For example, human-derived keratin is a typical protein that occurs in a bathroom environment. Proteins have hydrophobic regions, positively charged regions, and negatively charged regions in their molecules, so they can adhere to inorganic materials such as glass and ceramics, resin materials, and metal materials that are commonly used as wet-area components, by hydrophobic action, electrostatic action, and the like. For this reason, proteins were considered to be the main contaminants. Then, the inventors came up with the idea that it is important to suppress the adhesion of proteins, which are such main contaminants, to the surface of components. Therefore, it was first confirmed that the adhesion of proteins can be suppressed by including a betaine structure on the surface of the component. However, it was found that by incorporating a betaine structure into the surface of a component, a specific problem occurs in the component used in an environment where water and contaminants containing organic and inorganic components adhere to the surface, and the water dries while the water and contaminants are mixed on the surface, and this cycle is repeated. That is, a new problem was found that by incorporating a betaine structure into the surface of a component, the formation of water stains is promoted. Therefore, it was found that by incorporating a hydrophilic anion structure in addition to the betaine structure into the surface of a component, the adhesion of proteins can be suppressed and at the same time the formation of water stains can be suppressed, thereby solving the above problem. The present invention is based on these findings. [Means for solving the problem]

[0009] The component according to the invention comprises: A member used in an environment where water and contaminants including organic and inorganic components adhere to a surface, and the water dries while the water and contaminants are mixed on the surface, the cycle being repeated, The member includes a substrate and a surface layer, The surface layer includes a structure represented by the following formula (A1) and a structure represented by the following formula (A2), [ka] [ka] In formula (A1), L1 is -COO-, -CONH-, -(CH2) m - (where m is a natural number), R1 is H or CH3; X1 is a functional group represented by the following formula (B) or the following formula (C), [ka] [ka] In formula (B), R3 and R6 each independently represent -(CH2) l - (l is a natural number from 1 to 10), R4 and R5 are each independently an organic group that contains C and H as essential components and O as an optional component, but does not contain N or S; In formula (C), R7 and R8 each independently represent -(CH2) l - (l is a natural number from 1 to 10), R9, R 10 , R 11 are each independently an organic group containing C and H as essential components and O as an optional component, and not containing N or S, In formula (A2), L2 is -COO-, -CONH-, -(CH2) m -(m is a natural number), -Ph-, R2 is H or CH3; X2 is a functional group represented by the following formula (D) or formula (E): [ka] [ka] In formula (E), R 12 is an organic group containing C and H as essential components and O as an optional component, and not containing N or S, The concentration of Si atoms obtained by measuring the surface of the member by X-ray photoelectron spectroscopy (XPS) is 1.0% or less. It is characterized by: Effect of the Invention

[0010] According to the present invention, a component is provided that can suppress the adhesion or fixation of dirt, particularly limescale and protein, to a surface in an environment in which water and contaminants including organic and inorganic components adhere to a surface and the water dries while the water and contaminants are mixed on the surface, and further allows the adhered dirt to be easily removed, i.e., with a small cleaning load, in an environment in which this cycle is repeated. [Brief description of the drawings]

[0011] [Figure 1] FIG. 2 is a schematic cross-sectional view of an example of a member according to the present invention. [Diagram 2] 1 is a micrograph of a component sample of Example 2. [Diagram 3] 1 is a micrograph of a member sample of Comparative Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Materials FIG. 1 is a schematic cross-sectional view of an example of a member according to the present invention (hereinafter, sometimes simply referred to as a "member") that is used in an environment in which water and contaminants containing organic and inorganic components adhere to the surface, and the water dries while the water and contaminants are mixed on the surface, and this cycle is repeated. The member 10 according to the present invention comprises a substrate 1. The member 10 further comprises a surface layer 2. The surface layer 2 is preferably located on the outermost surface of the member 10. The member 10 may further comprise an intermediate layer 3 and / or a primer layer 4, which will be described later. The member 10 may further comprise layers other than those described above (not shown) within a range in which the effects of the present invention can be achieved. The presence of the surface layer 2 in the member 10 can be confirmed by observing the cross section of the member 10 using an electron microscope and separating the layers.

[0013] Purpose The member according to the present invention can be generally applied to members used in wet areas. Examples of wet areas include bathrooms, toilets, washrooms, and kitchens. Specific examples of wet area members for bathrooms include floors, bathtubs, walls, ceilings, counters, aprons, drains, mirrors, etc.; for toilets, toilet bowls, tanks, toilet lids, toilet seats, heated toilet seats, etc.; for washrooms, wash basins, wash counters, mirrors, lighting, plumbing fixtures, drains, cabinets, washing machine pans, etc.; for kitchens, sinks, counters, plumbing fixtures, drains, dishwashers, dish dryers, cooking ranges, kitchen hoods, ventilation fans, etc.

[0014] The member according to the present invention is a member used in an environment where a cycle is repeated in which water and pollutants containing organic and inorganic components adhere to the surface, and the water dries in a state where the water and pollutants are mixed on the surface. Preferably, the member is used in the above environment indoors. For example, the member is used in an environment where a cycle is repeated in which water, components constituting limescale (silicic acid ions, calcium ions, etc.) and proteins adhere to the surface of the member, and the water dries in a state where they are mixed. In addition, the present invention is applicable in a situation where the above cycle is repeated. For example, in the case where the member is a bathtub, the filled state (a state where water and pollutants adhere to the surface) and the drained state (a state where water dries in a state where water and pollutants are mixed) may be maintained in one state for a long time and then transition to another state, or the two states may exist unevenly, but the present invention is applicable even in such cases. The member according to the present invention can effectively suppress not only protein adhesion but also limescale adhesion in such an environment. Here, the contaminant refers to all kinds of dirt that adheres to the surface of a member used in an environment where water is repeatedly attached and dried, and more specifically, means one or more selected from silicate ions, calcium ions, sebum, soap scum, rinse, and protein. The member according to the present invention can be used with any substrate material that is generally used in a member used in an environment where water and contaminants are attached and the water dries in a mixed state, regardless of the type of substrate, and can achieve the above-mentioned effects on various substrates.

[0015] surface layer In the present invention, the surface layer contains a structure represented by the following formula (A1) and a structure represented by the following formula (A2). [ka] [ka] In formula (A1), L1 is -COO-, -CONH-, -(CH2) m- (where m is a natural number), R1 is H or CH3; X1 is a functional group represented by the following formula (B) or the following formula (C), [ka] [ka] In formula (B), R3 and R6 each independently represent -(CH2) l - (l is a natural number from 1 to 10), R4 and R5 are each independently an organic group that contains C and H as essential components and O as an optional component, but does not contain N or S; In formula (C), R7 and R8 each independently represent -(CH2) l - (l is a natural number from 1 to 10), R9, R 10 , R 11 are each independently an organic group containing C and H as essential components and O as an optional component, and not containing N or S, In formula (A2), L2 is -COO-, -CONH-, -(CH2) m -(m is a natural number), -Ph- (phenyl group), R2 is H or CH3; X2 is a functional group represented by the following formula (D) or formula (E): [ka] [ka] In formula (E), R 12 is an organic group containing C and H as essential components, O as an optional component, and containing no N or S.

[0016] Since the surface layer contains the structure represented by formula (A1) and the structure represented by formula (A2), the member according to the present invention can suppress the adhesion of various contaminants to the surface. In particular, it is possible to suppress both the adhesion of proteins and the fixation of limescale. The mechanism of these suppressions is thought to be as follows, but this is merely a hypothesis, and the present invention is not limited by this hypothesis in any way. The structure represented by formula (A1) is a betaine structure, as described below, and has anti-fouling properties (the ability to suppress the adsorption of proteins). This performance makes it possible to suppress the adhesion of proteins to the surface of the member. On the other hand, the N in the structure represented by formula (A1) + There is a risk that silicate ions are electrostatically adsorbed to the site. In this case, the amount of silicate ions attached increases. That is, the attachment density of silicate ions increases. This induces or promotes polymerization by dehydration condensation between silicate ions, and if the attachment density of silicate ions further increases in this state, the generated polymer becomes denser, which may accelerate the adhesion of water stains. However, since the surface layer of the member according to the present invention contains a structure represented by formula (A2) in addition to the structure represented by formula (A1), it is possible to suppress polymerization of silicate ions and further densification of the generated polymer. That is, since the structure represented by formula (A2) is a hydrophilic and anionic structure as described later, in the region in the surface layer where the hydrophilic and anionic structure exists, the same anionic silicate ions are electrostatically repelled. Therefore, the silicate ions cannot be adsorbed to the above region. In the surface layer of the member according to the present invention, the hydrophilic and anionic structure represented by formula (A2) and the betaine structure represented by formula (A1) coexist (for example, both are randomly present). Therefore, N in the structure represented by formula (A1) +Even if there are sites where silicate ions are attached to the surface of the substrate, there are also sites where the adsorption of silicate ions is inhibited due to the hydrophilic and anionic structure. Therefore, polymerization of silicate ions and further densification of the generated polymer can be blocked at these sites, and the adhesion of limescale can be suppressed. In this way, by including the structure represented by formula (A1) and the structure represented by formula (A2), the member according to the present invention can simultaneously suppress not only the adhesion of proteins but also the adhesion of limescale.

[0017] In the present invention, the surface layer containing a structure represented by formula (A1) means that the surface layer contains one or more types of structures represented by formula (A1), and the surface layer containing a structure represented by formula (A2) means that the surface layer contains one or more types of structures represented by formula (A2).

[0018] In the present invention, the surface layer is preferably a polymer layer. The polymer layer is a layer containing a polymer compound. In the present invention, the surface layer preferably contains a polymer compound containing a structure represented by formula (A1) and a structure represented by formula (A2), and it is more preferable that the structure represented by formula (A1) and the structure represented by formula (A2) are randomly bonded. That is, the surface layer preferably contains a random copolymer. The state of random bonding can be determined by observing the surface to see that the structure represented by formula (A1) or the structure represented by formula (A2) is not locally unevenly distributed. It is even more preferable that the surface layer contains a polymer compound containing only the structure represented by formula (A1) and the structure represented by formula (A2). In this case, it is preferable that the structure represented by formula (A1) and the structure represented by formula (A2) are randomly bonded.

[0019] The surface layer contains a random copolymer, 13Using C-NMR, it is possible to perform qualitative analysis of copolymer species and quantitative analysis of monomer sequence fraction (mol), monomer composition ratio (mol%, wt%), etc. For example, when the structure represented by formula (A1) is Z and the structure represented by formula (A2) is S, if a ZSZ or SZS sequence is present, the surface layer contains a random copolymer.

[0020] The structure represented by formula (A1) and the structure represented by formula (A2) will be further explained.

[0021] A structure represented by formula (A1) In formula (A1), L1 is preferably -COO-. This can further suppress protein adhesion and water stain adhesion. When L1 is -CONH-, protein adhesion or water stain adhesion may occur starting from the N that constitutes -CONH-. Also, when L1 is -(CH2) m If -, the hydrophobicity is increased and protein adhesion may occur.

[0022] In X1 of formula (A1), that is, in formula (B) or formula (C), l of R3, R6, R7, and R8 is preferably 1 to 6, more preferably 1 to 5, and even more preferably 1 to 3. This allows cationic N + Adsorption of anionic silicate ions and / or anionic SO3 - Site or PO4 - The adsorption of cationic calcium ions to the site can be minimized. This allows the structure represented by formula (A1) to form a stable molecule. That is, the cationic N + The anionic SO3 site at the end of the structure represented by formula (A1) - PO4 in the site or formula (A1) -Since the distance from the site is not too large, the anionic silicate ions and / or cationic calcium ions are prevented from easily approaching the structure represented by formula (A1) (i.e., the surface layer), and the adsorption of the anionic silicate ions and / or cationic calcium ions can be suppressed.

[0023] R4, R5, R9, R 10 , R 11 is preferably any one of an alkyl group, a hydroxyalkyl group, a carboxyalkyl group, a group represented by the following formula (H1), and a group represented by the following formula (H2). [ka] In formula (H1), p is a natural number. [ka] In formula (H2), q is a natural number. R4, R5, R9, R 10 , R 11 When is one of these organic groups, it is easy to synthesize a monomer that serves as a raw material for the structure of formula (B) or formula (C).

[0024] Also, R4, R5, R9, R 10 , R 11 is more preferably a methyl group. The monomers that are the raw materials for formula (B) or formula (C) are commercially available, and therefore are highly available. In addition, the concentration of organic groups, to which organic components such as proteins tend to adhere, in the surface layer can be reduced.

[0025] A structure represented by formula (A2) In formula (A2), X2, that is, formula (E), R 12 is preferably a linear or branched chain hydrocarbon group having a carbon number of 1 to 6, preferably 1 to 5. This can reduce the concentration of alkyl chains in the surface layer to which organic components such as proteins tend to adhere, thereby improving the effect of inhibiting adhesion of organic components such as proteins to the surface layer.

[0026] In the present invention, the surface layer containing the structure represented by formula (A1) and the structure represented by formula (A2) can be specified by any one of the following methods or a combination of multiple methods.

[0027] (Infrared Spectroscopy (IR)) By measuring the infrared light absorption spectrum near the surface of the surface layer using infrared spectroscopy, the functional groups contained in the surface layer can be estimated. For example, it is possible to identify the presence of -C=O and -CO- in an ester bond (-COO-) from the absorption wavenumber. Methods for measuring the infrared absorption spectrum near the surface of the surface layer include a method in which the surface layer is scraped off and collected, and the powder is measured using a transmission method, and more convenient methods include a single reflection ATR method and a microscopic ATR method.

[0028] (Time-of-flight secondary ion mass spectrometry (TOF-SIMS)) TOF-SIMS can provide structural information about organic matter present on the surface of the surface layer. By evaluating the surface layer with TOF-SIMS, it is possible to identify partial structures from fragment peaks specific to the structure represented by formula (A1) and the structure represented by formula (A2). For example, when the structure represented by formula (A1) is the structure represented by the following formula (A1-1), fragment peaks specific to m / z=279.11 and m / z=421.26 can be detected. Also, when the structure represented by formula (A2) is the structure represented by the following formula (A2-1), fragment peaks specific to m / z=79.96 can be detected. When measuring with TOF-SIMS, in order to remove dirt from the sample surface to be measured, the sample surface is sputtered to a depth of several nm with an ion source such as a gas cluster ion beam (GCIB) as a pretreatment, and then Bi3 2+ The primary ion source is irradiated with the sample and the resulting fragments are measured. [ka] [ka]

[0029] (X-ray photoelectron spectroscopy (XPS)) By XPS under the XPS measurement conditions described later, it is possible to identify the composition ratio and chemical bond state of C, N, O, S, P, and Si contained in the molecules constituting the surface layer. For example, the XPS spectrum (N1s orbital) of N atoms derived from a sulfobetaine structure as shown in formula (A1-1) has a peak position at a binding energy of 401.5 eV when no other ionic mixtures are present. In contrast, when the structure represented by formula (A1) is a structure as shown in the following formula (A3) (a structure containing a cationic ammonium moiety) or a mixture of formula (A3) and the above formula (A2-1) (a structure containing an anionic sulfonic acid moiety), the peak positions are 402.0 eV and 401.8 eV, respectively. In this way, it is possible to identify whether or not an N atom is derived from sulfobetaine based on the difference in peak position. Similarly, it is possible to identify whether S atoms are derived from sulfobetaine from the peak position. The XPS spectrum (S2p orbital) of S atoms derived from the structure shown in formula (A1-1) has a peak position at a binding energy of 166.2 eV, whereas the peak positions are 167.5 eV and 167.1 eV for the structure shown in formula (A2-1) (anionic sulfonic acid) or a mixture of formula (A3) and formula (A2-1). All of these peak positions are obtained by correcting with the peak position of the C1s orbital at 284.5 eV. [ka]

[0030] (Nuclear magnetic resonance measurement (NMR)) NMR can provide information on the bonding state of H, C, and N contained in the molecules that make up the surface layer and their interactions with neighboring atoms through chemical shifts compared with standard samples, allowing the molecular structure that makes up the surface layer to be identified in detail.

[0031] Static contact angle of the surface layer In the present invention, it is preferable that the static contact angle of water with respect to the surface of the surface layer is lower. Specifically, it is preferably 35° or less, more preferably 30° or less, and even more preferably 20° or less. Thereby, since the hydrophilicity is enhanced, it becomes possible to prevent the adhesion of various contaminants including proteins.

[0032] The static contact angle of water with respect to the surface of the surface layer is measured under the following measurement conditions using, for example, the following apparatus and software. Apparatus: DMo-702 (manufactured by Kyowa Interface Science Co., Ltd.) Software: Interface Measurement / Analysis Integrated System FAMAS Version: 7.3.0 Measurement method: Droplet method Droplet volume: 2.0 μL Waiting time: 1000 ms Analysis method: θ / 2 method

[0033] Proportion of the structure represented by formula (A1) (betaine structure) in the surface layer In the present invention, the abundance ratio (betaine ratio) of the structure (betaine structure) represented by the formula (A1) in the surface layer is preferably 16% or more and 55% or less. Thereby, the adhesion of proteins and the adhesion of scale can be favorably suppressed.

[0034] <Betaine ratio> The betaine ratio is calculated from the S atom concentration, P atom concentration, and N + N atom (hereinafter referred to as "N + atom") concentration attributed to the N atom obtained by XPS measurement described later. Since the N + atom and P atom are contained only in the betaine structure, and the S atom is contained in both the betaine structure and the structure (anion structure) represented by the formula (A2), the betaine ratio can be calculated as follows. Betaine ratio (%) = 100 × [N + atom concentration / (S atom concentration + P atom concentration)]

[0035] <XPS measurement> · Preparation of measurement sample A plate-shaped area of ​​an appropriate size can be cut from the component sample to be used as the measurement sample. It is preferable to clean the surface of the measurement sample before measurement. For example, it is more preferable to clean the surface of the measurement sample with a neutral detergent and a sponge, then perform ultrasonic cleaning with ultrapure water, and then rinse thoroughly with ultrapure water. ·XPS measurement device As the XPS measurement device, K-alpha (manufactured by ThermoFisher Scientific Co., Ltd.) can be used. XPS measurement conditions X-ray conditions: Monochromatic AlKα radiation, 72W-12KV Photoelectron extraction angle: 90° Analysis area: 400μmφ Neutralization gun conditions: 200μA Ion gun condition: 10mA (survey) Time per step: 10 ms Energy step size: 1.000eV Sweep: 2 times Pass energy: 200eV Scan range: -10~1350eV (Narrow) Time per step: 50 ms Energy step size: 0.100 eV Sweep: 5 times Pass energy: 50 eV Scan range: C1s peak 279.000eV~298.000eV, O1s peak 525.000eV~545.000eV, N1s peak 392.000eV~410.000eV, S2p peak 157.000eV~175.000eV, Si2p peak 95.000eV~110.000eV, P2p peak 124.000eV~144.000eV

[0036] <Calculation of each atomic concentration (S, N, Si, P)> The atomic concentration of the detected elements can be calculated from the obtained spectrum using, for example, data analysis software Thermo Avantage (version 5.9916, manufactured by Thermo Fisher Scientific Co., Ltd.). First, using the spectrum obtained from the survey analysis, check whether the cleaning has been properly performed. Next, for the spectrum obtained from the narrow analysis, perform charge correction with the C1s peak set at 284.5 eV. Then, after removing the background by the Smart method for the peaks based on the electron orbits of the measured atoms, calculate the peak area intensity and perform an analysis process of dividing by the sensitivity coefficient specific to the device preset in the data analysis software, and calculate the atomic concentration of each atom when the total of C atoms, O atoms, N atoms, S atoms, Si atoms, and P atoms is 100%.

[0037] <Separation of N atom peaks> For separating the peak derived from the +1-valent N atom (N + ) contained in the betaine structure from the peak derived from the other 0-valent N atom (N 0 ), the following method can be used. Fix the peak position of N + at 401.4 - 401.8 eV and the full width at half maximum of the peak at 1.6 eV, and fix the peak position of N 0 at 398.7 - 399.4 eV, and perform peak fitting. From the result of the peak fitting, calculate the atomic concentration of each of N + and N 0 .

[0038] The following conditions can be used for peak fitting. <Peak fitting conditions> Fitting Algorithm:Powell Maximum Iterations:90 Convergence:1e - 05 Gauss - Lorentz Mix:Product

[0039] Concentration of Si atoms In the present invention, the concentration of Si atoms obtained by XPS measurement of the surface of the member is 1.0% or less. The low concentration of Si atoms contained in the surface of the member can suppress the formation and adsorption of water stains. The concentration of Si atoms is preferably 0.4% or less.

[0040] S atom concentration In the present invention, when only those structures represented by formula (A1) in which X1 is a functional group represented by formula (B) are used, it is preferable that the concentration of S atoms obtained by XPS measurement of the surface of the member is 0.6% or more. This makes it possible to suppress the adsorption of proteins. The concentration of S atoms is preferably 0.7% or more. The concentration of S atoms is considered to be the total concentration of S in the functional group represented by formula (B) and S in the structure represented by formula (A2) that are present on the surface of the member.

[0041] P atom concentration In the present invention, when only those structures represented by formula (A1) in which X1 is a functional group represented by formula (C) are used, it is preferable that the concentration of P atoms obtained by XPS measurement of the surface of the member is 0.6% or more. This makes it possible to suppress the adsorption of proteins. The concentration of P atoms is preferably 0.7% or more. The concentration of P atoms is considered to be the concentration of P in the functional group represented by formula (C) that is present on the surface of the member.

[0042] Sum of the concentration of S atoms and the concentration of P atoms In the present invention, when both the structure represented by formula (A1) in which X1 is a functional group represented by formula (B) and the structure represented by formula (C) are used, it is preferable that the total concentration of S atoms and P atoms obtained by XPS measurement of the surface of the member is 0.6% or more. This makes it possible to suppress the adsorption of proteins. The concentration of S atoms is considered to be the total concentration of S in the functional group represented by formula (B) and S in the structure represented by formula (A2) that are present on the surface of the member.

[0043] N + Atomic Concentration In the present invention, the N + The concentration of the atoms is preferably 0.3% or more and 1.6% or less, and more preferably 0.4% or more and 1.5% or less.

[0044] In the present invention, the surface layer may be provided on the substrate, i.e., on the surface of the substrate. In other words, the surface layer may be formed directly on the surface of the substrate without including any other layer between the substrate and the surface layer. When the surface layer is provided on the surface of the substrate, the surface layer is preferably a gradient film with a gradient composition. Specifically, the surface side of the surface layer preferably includes a structure represented by formula (A1) and a structure represented by formula (A2), and the substrate side of the surface layer preferably includes a gradient film whose main chain contains a large amount of acrylic resin or polyvinyl resin, as described later. This makes it possible to ensure close contact with the substrate while suppressing the adsorption of proteins and the formation or adsorption of water stains.

[0045] Composition for forming surface layer In the present invention, the surface layer is preferably a cured surface layer forming composition. In the present invention, the surface layer forming composition may contain a compound having a betaine structure, an anionic monomer, a polymerization initiator, and a solvent as an optional component.

[0046] Compounds with a betaine structure In the present invention, the composition for forming a surface layer can contain a compound having a betaine structure. This allows the surface layer obtained by curing the composition for forming a surface layer to contain a structure represented by formula (A1). In the present invention, a compound having a betaine structure means a compound having at least one or more cations, anions, and ethylenically unsaturated groups in the same molecule. In the present invention, examples of the cation include quaternary ammonium, sulfonium, and phosphonium cations. Examples of the anion include -COO - , -PO4 2-, -HPO4 - , -SO3 - Examples of anions include:

[0047] In the present invention, the compound having a betaine structure contains a quaternary ammonium as a cation in the molecule and -SO3 as an anion. - Sulfobetaines containing quaternary ammonium as the cation and -PO4 as the anion 2- Among them, phosphobetaines containing quaternary ammonium as a cation and -SO3 as an anion are preferred. - More preferred is a sulfobetaine containing the following: Still more preferred is a sulfobetaine having a (meth)acrylic skeleton in the molecule.

[0048] In the present invention, an example of a compound having a betaine structure is compound 1 represented by the following formula (F1). Compound 1: [ka] In Compound 1, L1 includes any one of -COO-, -CONH-, and -(CH2)m- (m is a natural number); R1 is H or CH3; R3 and R6 each independently represent -(CH2) l - (l is a natural number from 1 to 10), R4 and R5 are each independently an organic group that contains C and H as essential components and O as an optional component, and does not contain N or S. It is characterized by: Incidentally, it is possible to specify that L1 contains -COO- from the above-mentioned IR.

[0049] In the present invention, an example of a compound having a betaine structure is compound 2 represented by the following formula (F2). Compound 2: [ka] In compound 2, L1 includes any one of -COO-, -CONH-, and -(CH2)m- (m is a natural number); R1 is H or CH3; R7 and R8 each independently represent -(CH2) l - (l is a natural number from 1 to 10), R9, R 10 , R 11 are each independently an organic group containing C and H as essential components and O as an optional component, and not containing N or S. It is characterized by:

[0050] In the present invention, specific examples of compounds having a betaine structure include 3-[[2-(acryloyloxy)ethyl]dimethylammonio]propane-1-sulfonic acid, 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1-sulfonic acid, 4-[(3-methacrylamidopropyl)dimethylammonio]butane-1-sulfonic acid, 2-(methacryloyloxy)ethyl 2-(trimethylammonio)ethyl] phosphate, 4-[[2-(methacryloyloxy)ethyl]dimethylammonio]butane-1-sulfonic acid, 3-[(3-acrylamidopropyl)dimethylammonio]propane-1-sulfonic acid, and 3-[(3-methacrylamidopropyl)dimethylammonio]propane-1-sulfonic acid. Among these, 3-[[2-(acryloyloxy)ethyl]dimethylammonio]propane-1-sulfonic acid, 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1-sulfonic acid, [3-(methacryloylamino)propyl]dimethyl(3-sulfobutyl)ammonium hydroxide, and 2-(methacryloyloxy)ethyl 2-(trimethylammonio)ethyl phosphate are preferred.

[0051] Anionic Monomers In the present invention, the composition for forming a surface layer can contain an anionic monomer. This allows the surface layer obtained by curing the composition for forming a surface layer to contain a structure represented by formula (A2). In the present invention, the anionic monomer means a compound having at least one anion and an ethylenically unsaturated group in the molecule. In the present invention, the anion is -COO - , -PO4 2- , -HPO4 - , -SO3 - Examples of anions include:

[0052] In the present invention, examples of the anionic monomer include anionic monomers represented by the following formulae (G1) and (G2). [ka] In formula (G1), L2 is -COO-, -CONH-, -(CH2) m -(m is a natural number), -Ph-, R2 is H or CH3; M represents a hydrogen ion, an ammonium ion, or an alkali metal ion. [ka] In formula (G2), L2 is -COO-, -CONH-, -(CH2) m -(m is a natural number), -Ph-, R2 is H or CH3; R 12 is an organic group containing C and H as essential components and O as an optional component, and not containing N or S, M represents a hydrogen ion, an ammonium ion, or an alkali metal ion.

[0053] In the present invention, specific examples of the anionic monomer include (meth)acryloyloxymethanesulfonic acid, potassium (meth)acryloyloxymethanesulfonate, sodium (meth)acryloyloxymethanesulfonate, 2-((meth)acryloyloxy)ethanesulfonic acid, potassium 2-((meth)acryloyloxy)ethanesulfonate, sodium 2-((meth)acryloyloxy)ethanesulfonate, 3-((meth)acryloyloxy)propane-1-sulfonic acid, potassium 3-((meth)acryloyloxy)propane-1-sulfonate, sodium 3-((meth)acryloyloxy)propane-1-sulfonate, 4-((meth)acryloyloxy)butane-1-sulfonic acid, potassium 4-((meth)acryloyloxy)butane-1-sulfonate, 4-((meth)acryloyloxy)butane-1-sulfonic acid, potassium 4-((meth)acryloyloxy)butane-1-sulfonate, 4-((meth)acryloyloxy)butane-1-sulfonic acid, ) acryloyloxy) butane-1-sulfonic acid sodium, 5-((meth)acryloyloxy) pentane-1-sulfonic acid, 5-((meth)acryloyloxy) pentane-1-sulfonic acid potassium, 5-((meth)acryloyloxy) pentane-1-sulfonic acid sodium, 6-((meth)acryloyloxy) hexane-1-sulfonic acid, 6-((meth)acryloyloxy) hexane-1-sulfonic acid potassium, 6-((meth)acryloyloxy) hexane-1-sulfonic acid sodium, 2-acrylamido-2-methylpropane sulfonic acid, 2-acrylamido-2-methylpropane sulfonic acid potassium, 2-acrylamido-2-methylpropane sulfonic acid sodium, styrene sulfonic acid, potassium styrene sulfonate, and sodium styrene sulfonate.

[0054] (solvent) In the present invention, the composition for forming a surface layer may contain a solvent. This can improve the wettability to the substrate or adjust the viscosity of the composition for forming a surface layer. As the solvent, alcohols such as methanol, ethanol, IPA (isopropanol), and n-butanol, cellosolves such as 2-methoxyethanol and methoxypropanol, ketones such as acetone, DMF (N,N'-dimethylformamide), water, etc. can be used, but are not limited to these. In addition, multiple types of solvents may be mixed and used as necessary. In addition, the solvent can also be used when preparing the composition for forming a primer layer and the composition for forming an intermediate layer, which will be described later.

[0055] (Polymerization initiator) The surface layer-forming composition preferably contains a polymerization initiator. As the polymerization initiator, known ones can be used, for example, a photopolymerization initiator or a thermal polymerization initiator.

[0056] Preferred examples of the photopolymerization initiator include Irgacure 651, Irgacure 184, Irgacure 500, Irgacure 2959, Irgacure 127, Irgacure 907, Irgacure 369, Irgacure 1300, Irgacure 819, Irgacure 1800, Irgacure OXE01, Irgacure OXE02, Darocur 1173, Darocur TPO, Darocur 4265, etc., all of which are provided by BASF. Note that in some cases, the trade names of these photopolymerization initiators have been changed from "Irgacure" or "Darocur" to "Omnirad."

[0057] As a preferred example of the thermal polymerization initiator, a thermal radical generator such as a peroxide, a persulfate, or an azo compound is preferably used.

[0058] (Additives) In addition to the above, the surface layer forming composition may contain known additives such as surfactants depending on the purpose, within the range that does not impair the function of the surface.

[0059] In one embodiment of the present invention, the surface layer may further contain a component contained in the intermediate layer described below, such as an acrylic resin (polyacrylic copolymer) or a polyvinyl copolymer.

[0060] Middle Tier In the present invention, in order to further strengthen the adhesion between the substrate 1 and the surface layer 2, an intermediate layer 3 may be formed between the substrate 1 and the surface layer 2. In order to obtain strong adhesion with the surface layer 2, which is an organic film, the intermediate layer 3 preferably contains an acrylic resin (polyacrylic copolymer) or a polyvinyl copolymer.

[0061] Composition for forming intermediate layer In the present invention, the intermediate layer 3 is preferably formed by curing a composition for forming an intermediate layer. The composition for forming an intermediate layer preferably contains a monomer capable of forming a polyacrylic or polyvinyl copolymer. The composition for forming an intermediate layer preferably further contains the above-mentioned solvent and polymerization initiator.

[0062] (Multifunctional acrylate) As a monomer constituting the polyacrylic copolymer, a multifunctional acrylate can be suitably used. In the present invention, the multifunctional acrylate means a monomer having at least two or more ethylenically unsaturated groups in the molecule. Specific examples of the multifunctional acrylate include 2-hydroxy-3-acryloyloxypropyl methacrylate, propoxylated ethoxylated bisphenol A diacrylate, ethoxylated bisphenol A diacrylate, 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene, propoxylated bisphenol A diacrylate, tricyclodecane dimethanol diacrylate, 1,10-decane diol diacrylate, 1,6-hexanediol diacrylate, 1,9-nonane diol diacrylate, and the like. All diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, ethoxylated isocyanuric acid triacrylate, ε-caprolactone modified tris-(2-acryloxyethyl) isocyanurate, pentaerythritol triacrylate, trimethylolpropane triacrylate, ditrimethylolpropane trimethacrylate, ethoxylated glycerin triacrylate, ethoxylated pentaerythritol tetraacrylate, ditrimethylolpropane trimethacrylate Pantaerythritol tetraacrylate, dipentaerythritol hexaacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, 2,2 bis [4- (methacryloxyethoxy) phenyl] propane, tricyclodecane dimethanol dimethacrylate, 1,10-decanediol dimethacrylate, 1,6-hexanediol methacrylate, 1,9-nonanediol methacrylate, neopentyl glycol methacrylate, glycerin dimethacrylate, trimethylolpropane trimethacrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, polypropylene glycol diacrylate, polytetramethylene glycol diacrylate, glycerin triacrylate ethoxylate, dipentaerythritol polyacrylate, ethoxylated polypropylene glycol dimethacrylate, polypropylene dimethacrylate, and the like.

[0063] In addition, the polyfunctional acrylate may be a urethane (meth)acrylate oligomer (polymer) having two or more ethylenically unsaturated groups. For example, phenyl glycidyl ether acrylate hexamethylene diisocyanate urethane prepolymer, phenyl glycidyl ether acrylate toluene diisocyanate urethane prepolymer, pentaerythritol triacrylate hexamethylene diisocyanate urethane prepolymer, pentaerythritol triacrylate toluene diisocyanate urethane prepolymer, pentaerythritol triacrylate isophorone diisocyanate urethane prepolymer, dipentaerythritol pentaacrylate hexamethylene diisocyanate urethane prepolymer, oligourethane acrylate, carboxylic acid-containing urethane acrylate oligomer, etc. may be mentioned.

[0064] In addition, examples of polyfunctional acrylates include epoxy (meth)acrylate oligomers (polymers) having two or more ethylenically unsaturated groups, such as cresol novolac type epoxy acrylates and carboxylic anhydride modified epoxy acrylates.

[0065] In the present invention, a specific example of a preferred polyfunctional acrylate is one in which the functional group equivalent of the ethylenically unsaturated group is 200 g / eq or less. This allows a primer layer with high durability to be obtained. The functional group equivalent of the ethylenically unsaturated group is preferably 150 g / eq or less, more preferably 27 g / eq or more and 150 g / eq or less. This allows a primer layer with higher durability to be obtained. Here, the functional group equivalent represents the molecular weight of a compound per functional group. That is, it is a value obtained by dividing the molecular weight of the polyfunctional acrylate by the number of ethylenically unsaturated groups. Specifically, it is a value obtained by dividing the molecular weight of the polyfunctional acrylate, which is a (meth)acrylate monomer (oligomer), a urethane modified product thereof, a urethane (meth)acrylate monomer (oligomer), and an epoxy modified product thereof, an epoxy (meth)acrylate monomer (oligomer), by the number of (meth)acryloyl groups, which are ethylenically unsaturated groups. Examples of compounds satisfying such functional group equivalents include pentaerythritol tetraacrylate (88 g / eq), dipentaerythritol tetraacrylate (105 g / eq), dipentaerythritol hexaacrylate (96 g / eq), trimethylolpropane triacrylate (99 g / eq), trimethylolpropane tetraacrylate (117 g / eq), 1,3,5-tris(2,2-diacryloyloxymethyl-3-(2,2,2-triacryloyloxymethylethoxy)propylhexylcarbamate)isocyanurate (153 g / eq), and ethoxylated dipentaerythritol hexaacrylate (185 g / eq).

[0066] Among these, those having six or more functional groups in one molecule are particularly preferred in order to further enhance the durability of the intermediate layer, and examples thereof include dipentaerythritol hexaacrylate (6 functional), ethoxylated dipentaerythritol hexaacrylate (6 functional), and 1,3,5-tris(2,2-diacryloyloxymethyl-3-(2,2,2-triacryloyloxymethylethoxy)propylhexylcarbamate)isocyanurate (15 functional).

[0067] (Polyfunctional vinyl compounds) As a monomer constituting the polyvinyl copolymer, a multifunctional vinyl compound can be suitably used. In the present invention, the multifunctional vinyl compound means a monomer having at least two ethylenically unsaturated groups in the molecule. Specific examples of the multifunctional vinyl compound include diallyl ether, diethylene glycol divinyl ether, 1,3-diallyloxy-2-propanol, 1,2,3-triallyloxy-2-propanol, 2,2 bisallyloxymethyl-1-propanol, 2,2 bisallyloxyethyl-1-butanol, 2,2 bisallyloxymethyl-1-hexanol, 3,3 bisallyloxyethyl-1-butanol, 3,3 bisallyloxyethyl-1-hexanol, 2, Examples of such alkyl ethers include 2,2-aryloxymethyl-1-ethanol, 2,2,2-aryloxymethyl-1-propanol, 2,2,2-aryloxymethyl-1-butanol, 2,2,2-aryloxymethyl-1-hexanol, 1,5-hexadiene-3,4-diol, diallyl isophthalate, 1,5-hexanediene, tetraallyloxyethane, tetraallyloxypropane, tetraallyloxybutane, triallyl citrate, and divinyl adipate.

[0068] graded layer In an embodiment in which the member according to the present invention further includes an intermediate layer between the substrate and the surface layer, the surface layer and the intermediate layer may be formed separately, as described below, or the surface layer and the intermediate layer may be formed simultaneously by using a composition in which a composition for forming a surface layer and a composition for forming an intermediate layer are mixed. In the latter case, it is necessary to form a film so that the structure represented by formula (A1) and the structure represented by formula (A2) are sufficiently (largely) contained in the surface layer of the integrated layer of the surface layer and the intermediate layer formed simultaneously. For example, by adding an additive such as a surfactant to the above-mentioned mixed composition and forming a film, the presence ratio of the structure represented by formula (A1) and the structure represented by formula (A2) in the surface side region of the integrated layer (corresponding to the surface layer) is made sufficiently higher than the presence ratio in the substrate side region of the integrated layer (corresponding to the intermediate layer), that is, it is possible to arrange the structure represented by formula (A1) and the structure represented by formula (A2) in a gradient arrangement in the surface side region of the integrated layer. In the present invention, the integrated layer in which the structure represented by formula (A1) and the structure represented by formula (A2) are arranged in a gradient arrangement in the surface side region is called a "gradient layer". The surfactant used to obtain the gradient layer is preferably one having a hydrophilic portion and a hydrophobic portion consisting of an organic residue, and having a molecular weight of less than 10,000.

[0069] In the present invention, the gradient layer includes a structure represented by formula (A1) and a structure represented by formula (A2), which are essential components of the surface layer, and a polyacrylic copolymer or a polyvinyl copolymer, which is an essential component of the intermediate layer. The preferred forms and the method of specifying the structure represented by formula (A1) and the structure represented by formula (A2) in the gradient layer are the same as those already explained for the surface layer. The preferred forms of the polyacrylic resin and the polyvinyl copolymer in the gradient layer are the same as those already explained for the intermediate layer. The gradient layer is characterized in that it contains many structures represented by formula (A1) and formula (A2) on its surface side, and many acrylic resins or polyvinyl resins on its substrate side. This makes it possible to ensure adhesion to the substrate while the surface of the member has high hydrophilicity, anti-fogging properties, and anti-fouling properties.

[0070] The ratio of the concentration of the structure represented by formula (A1) and formula (A2) on the surface of the gradient layer to the concentration of the structure represented by formula (A1) and formula (A2) inside the gradient layer When the surface of the inclined layer is taken as the point with a film thickness depth of 0 and the interface between the inclined layer and the substrate is taken as the point with a film thickness depth of 1, the ratio (B / S) of the existence ratio (B) of the structure represented by Formula (A1) and Formula (A2) at the film thickness depth of 1 / 10 point to the existence ratio (S) of the structure represented by Formula (A1) and Formula (A2) at the film thickness depth of 0 point is preferably 0 or more and less than 1, more preferably 0 or more and less than 0.8, and even more preferably 0 or more and less than 0.6. Note that the concentration ratio of the structures represented by Formula (A1) and Formula (A2) on the surface and inside of the inclined layer can be measured by the following method.

[0071] <Gas Cluster Ion Beam - X-ray Photoelectron Spectroscopy (GCIB-XPS)> The inclined layer is sputtered with Ar gas cluster ions, and the surface exposed at each specific sputtering time is measured by XPS, and the depth distribution of the structure represented by Formula (A1) and Formula (A2) can be measured by calculating the concentration of S atoms or the total of the concentration of S atoms and the concentration of P atoms. From the measured depth distribution, the concentration ratio of the structures represented by Formula (A1) and Formula (A2) on the surface and inside of the inclined layer can be calculated.

[0072] <GCIB-XPS Measurement Method> · Preparation of Measurement Sample A flat plate-shaped region cut from the member sample with an appropriate size can be used as the measurement sample. It is preferable to clean the surface of the measurement sample before measurement. For example, it is more preferable to clean the surface of the measurement sample using a neutral detergent and a sponge, then perform ultrasonic cleaning with ultrapure water, and then thoroughly rinse with ultrapure water. · XPS Measurement Device As the XPS measurement device, QUANTERA II (manufactured by ULVAC-PHI, Inc.) can be used. · XPS Measurement Conditions X-ray Conditions: Monochromatized AlKα ray, 25W - 15KV Photoelectron Extraction Angle: 45° Analysis Region: 100μmφ Neutralizing Gun Conditions: Auto Neutralizer Ion gun conditions: Auto Neutralizer (narrow) Time per step: 50 ms Energy step size: 0.100 eV Sweep: 5 times Pass energy: 55 eV Scan range: C1s peak 279.000eV~299.000eV, O1s peak 525.000eV~545.000eV, N1s peak 392.000eV~410.000eV, S2p peak 157.000eV~177.000eV, P2p peak 124.000eV~144.000eV GCIB sputtering conditions The following conditions can be used for GCIB sputtering: Beam voltage: 10kV Beam current: 30nA

[0073] <Calculation of each atomic concentration (S, P)> The atomic concentration of the detected elements can be calculated from the obtained spectrum using, for example, the data analysis software MultiPaK (version 9.0, manufactured by ULVAC-PHI, Inc.). The spectrum obtained by narrow analysis is charge-corrected with the C1s peak set at 284.5 eV. Then, the background is removed by the Shirley method for the peaks based on the electron orbitals of each measured atom, and the peak area intensity is calculated. An analysis process is performed in which the peaks are divided by the sensitivity coefficient specific to the device that is preset in the data analysis software, and the concentration of each atom is calculated when the sum of C atoms, O atoms, N atoms, S atoms, and P atoms is set to 100%.

[0074] The ratio of the abundance ratio of the structures represented by formulas (A1) and (A2) on the surface and inside of the gradient layer can be calculated using the concentration of S atoms or the sum of the concentrations of S atoms and P atoms. In other words, the ratio (B / S) of the abundance ratio (B) of the structures represented by formulas (A1) and (A2) at a film thickness depth of 1 / 10 to the abundance ratio (S) of the structures represented by formulas (A1) and (A2) at a film thickness depth of 0 can be calculated in the following two ways.

[0075] When X1 in the structure represented by formula (A1) is a functional group represented by formula (C), B / S can be calculated by the ratio of the sum of the concentration of S atoms (S1) and the concentration of P atoms (P1) at a point 1 / 10 of the film thickness depth to the sum of the concentration of S atoms (S0) and the concentration of P atoms (P0) at a point 0 in the film thickness depth, as shown in the following formula. B / S=(S1+P1) / (S0+P0)

[0076] When X1 in the structure represented by formula (A1) is not a functional group represented by formula (C), i.e., when X1 is a functional group represented by formula (B), B / S can be calculated by the ratio of the total concentration of S atoms (S1) at a point 1 / 10 of the film thickness depth to the concentration of S atoms (S0) at a point 0 in the film thickness depth, as shown in the following formula. B / S=S1 / S0

[0077] Composition for forming a gradient layer In the present invention, the gradient layer is preferably a cured composition for forming a gradient layer. The composition for forming a gradient layer preferably contains the above-mentioned compound having a betaine structure, an anionic monomer, a polymerization initiator, a monomer capable of forming a polyacrylic or polyvinyl copolymer, and, as optional components, a solvent and a surfactant.

[0078] The surfactant is preferably a polymerizable surfactant in order to improve the wettability of the surface. Examples of the polymerizable surfactant include polyoxypropylene allyl ether phosphate ester, ammonium salt of sulfuric acid and ethoxylated allyl alkyl glyceryl ether ester, polyoxyalkylene alkenyl ether, sodium alkyl allyl sulfosuccinate, polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ester ammonium salt, and amine salt.

[0079] In the present invention, the film thickness including the formed surface layer and intermediate layer or the film thickness of the inclined layer is preferably in the range of 0.1 μm to 200 μm. Thereby, the effects of suppressing the adhesion of proteins and the adhesion of scale can be sufficiently obtained, and further, the abrasion resistance can be exhibited. The film thickness including the surface layer and intermediate layer is more preferably in the range of 1 to 100 μm, and even more preferably in the range of 1 to 20 μm.

[0080] The film thickness of the surface layer can be measured by cross-sectional observation using SEM or the like.

[0081] <Film Thickness Measurement by SEM> ·SEM apparatus For the SEM apparatus, Regulus8220 (manufactured by Hitachi High-Technologies Corporation) can be used and measurement can be performed under the following conditions. ·SEM measurement conditions Acceleration voltage: 1 kV Magnification: 20000 to 400 times

[0082] Primer layer In the present invention, when the base material 1 is an inorganic material such as glass, pottery, or metal, a primer layer 4 may be formed in order to strengthen the adhesion between these inorganic materials and the surface layer 2. The primer layer 4 is preferably formed between the inorganic material which is the base material 1 (hereinafter referred to as "inorganic base material") and the surface layer 2. In order to enhance the adhesive strength, the primer layer 4 needs to bond to both the inorganic base material and the surface layer 2. For this reason, the primer layer 4 is preferably a layer containing silicon atoms.

[0083] Primer layer forming composition The primer layer 4 is preferably formed by curing a composition for forming a primer layer. As the composition for forming a primer layer, it is possible to use those containing commonly used silane-based or phosphoric acid-based coupling agents. Further, in order to make the adhesion to the surface layer stronger, these coupling agents preferably contain ethylenically unsaturated groups such as acryloyl groups and methacryloyl groups.

[0084] (Silane compounds) Silane compound can be suitably used as silane coupling agent. In the present invention, silane compound means an organic compound having hydrolyzable Si-OR group (reactive silyl group, OR can be hydroxyl group or hydrolyzable group. Hydrolyzable group is, for example, alkoxy group, halogeno group. Specifically, -OCH3, -OCH2CH3, -Cl can be mentioned.). Specific examples of silane compounds include tetraethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, 8-methacryloxyoctyltrimethoxysilane, 3-methacryloxymethyltriethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxymethyltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, Silane, 3-glycidoxypropyltriethoxysilane, p-styryltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, tris-(trimethoxysilylpropyl)isocyanurate, 3-ureidopropyltrialkoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-isocyanatopropyltriethoxysilane, 3-trimethoxysilylpropylsuccinic anhydride, and the like.

[0085] In the present invention, a specific example of a preferred silane compound is a compound having three or more hydrolyzable Si-OR groups for adhering to an inorganic substrate and an acrylic or methacrylic polymerizable functional group for adhering to a surface layer that is an organic film. Examples of such silane compounds include 3-acryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, 8-methacryloxyoctyltrimethoxysilane, 3-methacryloxymethyltriethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-methacryloxymethyltrimethoxysilane.

[0086] (Phosphate Compounds) As the phosphate coupling agent, a phosphate compound can be preferably used. In the present invention, the phosphate compound is a compound having a covalent bond P(OH) n It means an organic compound having a group (adsorbent phosphate group, n is any one of 1 to 3, and OH group may be its base substitute such as ONa, OK, ONH4, etc.). As the phosphate compound, those containing phosphoric acid or a phosphate as an adsorbent functional group and an acryl group, methacryl group, or vinyl group as a polymerizable functional group in the molecule are preferable. Specific examples include 2-acryloxyethyl phosphoric acid, 2-acryloxyethyl phosphoric acid, 2-methacryloxyethyl phosphoric acid, 2-methacryloxyethyl phosphoric acid, 2-acryloxypropyl phosphoric acid, 2-acryloxypropyl phosphoric acid, 2-methacryloxypropyl phosphoric acid, 2-methacryloxypropyl phosphoric acid, 2-methacryloxypropyl phosphoric acid, vinyl phosphoric acid, 2-acryloxybutyl phosphoric acid, 2-acryloxybutyl phosphoric acid, 2-methacryloxybutyl phosphoric acid, 2-methacryloxybutyl phosphoric acid, vinyl phosphoric acid, or their phosphates.

[0087] (optional ingredient) Other optional components may be added to the surface layer, intermediate layer, gradient layer, and primer layer, such as ultraviolet absorbers, light stabilizers, antioxidants, leveling agents, defoamers, thickeners, anti-settling agents, and various additives such as dyes, pigments, and matting agents that control the design properties of the paint, within a range that does not impair the stain resistance of the member.

[0088] Base material In the present invention, the substrate is not particularly limited. As the material of the substrate, any material generally used as a water-related component, such as resin, metal, inorganic material (glass, ceramic, etc.), can be used. In addition, the shape of the substrate can be a general shape of a water-related component. For example, it may be a flat plate or a complex shape.

[0089] Surface properties of the component When the member according to the present invention is used in a wet area, the member is maintained by, for example, rubbing the member with a sponge or cloth soaked in water and a detergent containing water. It is more preferable that the member according to the present invention has a static contact angle of water on the surface layer of 35 degrees or less after the sliding durability evaluation test described below is carried out. This allows the member to have sufficient sliding durability, and the effect of suppressing adhesion of protein and fixation of water stains can be maintained for a long period of time even in the above-mentioned environment.

[0090] <Sliding durability evaluation> The member according to the present invention can be subjected to a sliding durability test using a sliding machine (manufactured by Tester Sangyo Co., Ltd.) according to the following method. A commercially available urethane sponge (Scotch-Brite Bath Shine, manufactured by 3M Japan Co., Ltd.) was soaked in a mixture of water and neutral detergent (Bath Magiclean, manufactured by Kao Corporation) in a weight ratio of 90:10, and subjected to a load of 25 [g / cm 2 ] is moved back and forth over the surface of the member 5000 times. After washing the member with running water, it is dried and the static contact angle of water is measured by the method described above.

[0091] <Protein adhesion area ratio> The protein adhesion inhibitory effect of the member according to the present invention can be indicated by using as an index the protein adhesion area ratio obtained according to the procedure described below.

[0092] (Preparation of protein-containing suspension) 2.5 g of commercially available wool keratin (Tokyo Chemical Industry Co., Ltd.) was mixed and suspended in 100 mL of ion-exchanged water, to which 0.25 g of triolein (Kanto Chemical Co., Ltd.) was added in order to increase the dispersibility of the keratin, and ultrasonic treatment was performed for 10 minutes in warm water at 40°C. Then, the mixture was centrifuged at 15,000 rpm for 10 minutes, and the supernatant was removed. Then, the same amount of ion-exchanged water as the removed supernatant was replenished. Then, ultrasonic treatment was performed for 10 minutes in warm water at 40°C to obtain a suspension.

[0093] (Protein adhesion and cleaning) After immersing the component in the suspension for 10 minutes, the component is taken out of the suspension. Then, ultrapure water is applied to the surface of the component using a dropper at a concentration of 0.4 [mL / cm 2 ] and wash. The component is then tilted at a 25° angle and dried for one hour. This procedure is repeated twice to obtain a component with keratin attached.

[0094] (Observation of the surface of a component with proteins attached) Using a laser microscope LEXT OLS5000 (Olympus Corporation), select 117x magnification and standard mode (pitch 1.2 μm) to capture images of 2580 μm × 2580 μm per field of view. The specifications of the microscope are as follows: Equipment:OLS5000 Product Version: 1.2.1.4807 Light source: 405nm semiconductor laser Detection system: Photomultiplier Objective lens: OLYMPUS MPlan APO N 5X / 0.15 LEXT

[0095] The black structure seen in the captured image is a protein to which the protein is attached. The attachment area ratio of the protein can be calculated by the method shown below.

[0096] (Calculation of protein attachment area ratio) The obtained image is used with the image processing library "OpenCV" (version: 4.5.5) to calculate the protein attachment area ratio. First, the image captured with a laser microscope is imported into the library, and after monochrome image processing, binarization processing is performed. Regarding the setting of the threshold value for the binarization processing, it is appropriately adjusted between pixel values 150 to 160 so that the attached protein is selected. Thereby, the total area ratio is calculated. This total area ratio is taken as the protein attachment area ratio.

[0097] The protein attachment area ratio of the member according to the present invention obtained as described above is preferably 8% or less. More preferably, it is 5% or less, and even more preferably, it is 1% or less.

[0098] In the member of the present invention, the concentration of Si atoms obtained by XPS measurement in the region from the outermost surface to a depth of 1 μm is preferably 1.0% or less, and more preferably 0.4% or less. Thereby, even when the surface is worn due to long-term use of the member and the intermediate layer is exposed, the formation, adsorption of scale, and attachment of contaminants such as proteins can be suppressed.

[0099] The concentration of Si atoms obtained by XPS measurement in the region from the outermost surface to a depth of 1 μm can be measured by any of the following methods.

[0100] <Gas cluster ion beam - X-ray photoelectron spectroscopy (GCIB-XPS)> The surface layer is sputtered with Ar gas cluster ions, and the surface exposed at each specific sputtering time is measured by XPS, and the concentration of Si atoms can be calculated.

[0101] <XPS measurement> · Preparation of measurement sample A flat plate-shaped region cut from a component sample in an appropriate size can be used as a measurement sample. It is preferable to clean the surface of the measurement sample before measurement. For example, it is more preferable to clean the surface of the measurement sample using a neutral detergent and a sponge, then perform ultrasonic cleaning with ultrapure water, and finally thoroughly rinse with ultrapure water. ·XPS measurement device For the XPS measurement device, QUANTERA II (manufactured by ULVAC-PHI, Inc.) can be used. ·XPS measurement conditions X-ray conditions: Monochromatic AlKα ray, 25W - 15KV Photoelectron extraction angle: 45° Analysis area: 100μmφ Neutralization gun conditions: Auto Neutralizer Ion gun conditions: Auto Neutralizer (narrow) Time per step: 50ms Energy step size: 0.100eV Sweep: 5 times Pass energy: 55eV Scanning range: C1s peak 279.000eV - 299.000eV, O1s peak 525.000eV - 545.000eV, N1s peak 392.000eV - 410.000eV, S2p peak 157.000eV - 177.000eV, P2p peak 124.000eV - 144.000eV ·GCIB sputtering conditions The following conditions can be used for GCIB sputtering. Beam voltage: 10kV Beam current: 30nA

[0102] <Calculation of atomic concentration of Si> The atomic concentration of the detected elements can be calculated from the obtained spectrum using, for example, data analysis software MultiPaK (version 9.0, manufactured by ULVAC-PHI, Inc.). The spectrum obtained by XPS measurement is charge-corrected with the C1s peak set at 284.5 eV. After that, the background is removed by the Shirley method for the peaks based on the electron orbitals of each measured atom, and the peak area intensity is calculated. An analysis process is performed in which the peaks are divided by the sensitivity coefficient specific to the device that is preset in the data analysis software, and the atomic concentration of Si is calculated when the sum of C atoms, O atoms, N atoms, S atoms, Si atoms, and P atoms is set to 100%.

[0103] The sputter rate can be calculated by dividing the actual depth of the sputter marks on the sample after measurement, which is observed with a laser microscope, by the sputter time. Also, the depth at that point can be calculated by integrating the sputter time and the sputter rate.

[0104] Manufacturing method of components The member according to the present invention can be produced, for example, by the following method.

[0105] <Preparing the substrate> A substrate is prepared. In the present invention, it is preferable to pretreat the substrate. For example, it is preferable to wash the substrate with a neutral detergent and rinse with ion-exchanged water or ultrapure water. Any water droplets remaining on the substrate surface are preferably dried using an air blower or a dryer.

[0106] <Preparation of Surface Layer Forming Composition> A compound containing a structure represented by formula (A1) (a compound having a betaine structure) and a compound containing a structure represented by formula (A2) (anionic monomer) as well as other components are mixed in any ratio and dissolved in a solvent. A polymerization initiator is added to this solution and stirred to obtain a composition for forming a surface layer. The total weight concentration of the compound containing a structure represented by formula (A1) and the compound containing a structure represented by formula (A2) is preferably 0.5% to 20%, and the weight concentration ratio of each in the composition is preferably 95:5 to 5:95.

[0107] <Coating of the composition for forming the surface layer> The composition for forming a surface layer is applied onto the substrate. A known method may be used as the application method. For example, the composition can be applied by a general method such as brush coating, spray coating, dip coating, spin coating, curtain coating, bar coating, etc. The coating amount can be adjusted according to these application conditions to adjust the film thickness of the resulting cured product. In the present invention, the film thickness of the formed surface layer (or including both the surface layer and the intermediate layer) is preferably in the range of 0.1 μm to 200 μm. This provides a sufficient effect of suppressing the adhesion of proteins and the adhesion of water stains, and further allows the abrasion resistance to be exhibited. The film thickness of the surface layer (or including both the surface layer and the intermediate layer) is more preferably in the range of 1 to 100 μm, and even more preferably in the range of 1 to 20 μm.

[0108] <Drying> The surface layer forming composition applied on the substrate is dried. In the present invention, when the surface layer forming composition contains a solvent, it is preferable to dry the surface layer forming composition after applying it on the substrate in order to dry the solvent. In addition, in consideration of the productivity of the member, drying by heating can be preferably used.

[0109] <Curing> The surface layer forming composition applied on the substrate is cured. Examples of the curing means include heat curing, active energy ray curing, and a combination of heat curing and active energy ray curing. When heat curing is performed, a known thermal polymerization initiator can be used as the polymerization initiator, and a known method of heating with infrared rays or hot air can be used. In addition, in the case of active energy ray curing, examples of the radiation include visible light of 400 to 800 nm, ultraviolet light of 400 nm or less, and electron beams. Usually, relatively inexpensive ultraviolet light or visible light is preferably used rather than electron beams, which require expensive equipment. When active energy ray curing is performed using ultraviolet light or visible light, a known photopolymerization initiator can be used. When ultraviolet light is used, examples of the ultraviolet light generating source include low pressure mercury lamps, high pressure mercury lamps, ultra-high pressure mercury lamps, xenon lamps, gallium lamps, metal halide lamps, ultraviolet lasers, and ultraviolet light such as sunlight. The irradiation atmosphere may be air or an inert gas such as nitrogen or argon.

[0110] <Formation of the intermediate layer> In the present invention, the intermediate layer 3 may be formed on the substrate 1 before the surface layer 2 is formed on the substrate 1. This can further strengthen the adhesion between the substrate 1 and the surface layer 2. The composition for forming the intermediate layer can be prepared, for example, by adding a polymerization initiator to a solution in which the monomer capable of forming the above-mentioned polyacrylic or polyvinyl copolymer and a solvent are dissolved at an arbitrary weight ratio, and then stirring the solution. The intermediate layer 3 can then be formed by applying the prepared composition for forming the intermediate layer on the substrate 1, drying, and curing it.

[0111] The thickness of the intermediate layer can be adjusted by the coating conditions, similarly to the surface layer. In the present invention, the thickness of the formed intermediate layer (or including both the surface layer and the intermediate layer) is preferably in the range of 0.1 μm to 200 μm. This provides a sufficient effect of suppressing the adhesion of proteins and the adhesion of water stains, and further allows abrasion resistance to be exhibited. The thickness of the intermediate layer (or including both the surface layer and the intermediate layer) is more preferably in the range of 1 to 100 μm, and even more preferably in the range of 1 to 20 μm.

[0112] <Formation of primer layer> In the present invention, when the substrate 1 is an inorganic material such as glass, pottery, or metal, a primer layer 4 may be formed on the inorganic substrate before forming an intermediate layer 3 on the inorganic substrate. This can further strengthen the adhesion between the inorganic substrate and the surface layer 2. The composition for forming a primer layer can be prepared, for example, by dissolving the above-mentioned coupling agent and a solvent, and, if necessary, a catalyst for promoting the hydrolysis reaction in an arbitrary weight ratio, and stirring the mixture. Thereafter, the prepared composition for forming a primer layer can be applied to the inorganic substrate and dried to form the primer layer 4. EXAMPLES

[0113] The present invention will be described in more detail with reference to the following examples, although the present invention is not limited to these examples.

[0114] 1. Preparation 1-1. Base material The following five types of substrates were prepared. Acrylic plate: Acrylite EX (manufactured by Mitsubishi Rayon Co., Ltd.) PET film: Lumirror Film T60 (manufactured by AS ONE Corporation) Glass: borosilicate glass · Ceramic: Sanitary ware with a glaze layer on the surface Metal: Brass plate with nickel-chrome plating on the surface

[0115] 1-2.Reagents The following reagents were prepared:

[0116] <Multifunctional acrylate> Dipentaerythritol polyacrylate

[0117] <Polymerization initiator> A mixture of 1-hydroxycyclohexyl phenyl ketone and benzophenone in a weight ratio of 1:1 (BASF Irgacure 500)

[0118] <Solvent> 2-Methoxyethanol

[0119] <Compounds with betaine structure> Betaine Monomer 1: 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1-sulfonic acid Betaine Monomer 2: 4-[(3-methacrylamidopropyl)dimethylammonio]butane-1-sulfonic acid Betaine monomer 3: 2-(methacryloyloxy)ethyl 2-(trimethylammonio)ethyl phosphate

[0120] <Anionic Monomer> Anionic monomer 1: Potassium 3-((meth)acryloyloxy)propane-1-sulfonate Anionic monomer 2: Sodium 2-acrylamido-2-methylpropanesulfonate Anionic monomer 3: Sodium p-styrenesulfonate

[0121] <Silane compounds> Silane compound 1: 3-acryloxypropyltrimethoxysilane Silane compound 2: 3-methacryloxypropyltrimethoxysilane

[0122] <Surfactant> Surfactant 1: Sodium di-2-ethylhexyl sulfosuccinate (Aerosol OT) The standard content was 75% by weight. Surfactant 2: Ammonium polyoxyalkylene alkenyl ether sulfate The standard content was 19-21% by weight.

[0123] 2. Preparation of component samples Examples 1 to 8 (Pretreatment) The surface of the acrylic plate, which is the substrate, was washed with a neutral detergent and rinsed with ion-exchanged water or ultrapure water. Water droplets on the surface of the substrate were blown off with an air blower, and the substrate was dried in a dryer at 60°C for 30 minutes.

[0124] (Middle class) A polymerization initiator was added at a weight concentration of 0.6% to a solution of multifunctional acrylate:solvent = 33:67 (weight ratio), and the mixture was stirred with a stirrer for 1 hour to prepare a composition for forming an intermediate layer. This composition was applied to the pretreated substrate by spin coating (1500 rpm, 15 seconds) or bar coating (#10) as shown in Table 1. Immediately after application, the substrate was placed in a hot air drying oven and allowed to stand at 60°C for 10 minutes. Thereafter, an ultraviolet ray irradiation device (MDB15001N-01, SunEnergy Co., Ltd.) was used to irradiate the substrate with an accumulated light dose of 1000 mJ / cm. 2 The applied surface was irradiated with UV light to cure so that the viscosity reached 100 ppm (measured using an ultraviolet integrating light meter, C9536-254, manufactured by Hamamatsu Photonics K.K.).

[0125] (Surface layer) A compound having a betaine structure and an anionic monomer shown in Table 1 were mixed in an arbitrary ratio and dissolved in a solvent so that the total of these was 10% by weight. A polymerization initiator was then added to this solution at a weight concentration of 0.2%, and the solution was stirred with a stirrer for 1 hour to prepare a composition for forming a surface layer. This composition was applied to the intermediate layer by spin coating (1500 rpm, 15 seconds) or bar coating (#10) as shown in Table 1. Immediately after application, the composition was placed in a hot air drying oven and left to stand at 60°C for 10 minutes. Thereafter, an ultraviolet ray irradiation device (MDB15001N-01, manufactured by Sun Energy Co., Ltd.) was used to obtain an integrated light dose of 3 J / cm. 2The applied surface was irradiated with UV light to cure so that the viscosity reached 100 ppm (measured using an ultraviolet integrating light meter, C9536-254, manufactured by Hamamatsu Photonics K.K.).

[0126] To remove uncured components, the specimen was washed with a neutral detergent, rinsed with ion-exchanged water or ultrapure water, and then left to dry at room temperature for at least 1 hour to obtain a component sample.

[0127] Example 9 A component sample was obtained in the same manner as in Example 1, except that the acrylic plate was replaced with a PET film as the substrate.

[0128] Examples 10 to 12 (Pretreatment) The inorganic substrates shown in Table 1 were used as substrates, and the substrate surfaces were activated by UV ozone treatment after drying in the same pretreatment as in Example 1. The UV ozone treatment was performed by irradiating UV ozone for 10 minutes using a UV ozone irradiation device (manufactured by Asumi Giken Co., Ltd.).

[0129] (Primer layer) A mixture of silane compound (1 or 2): 10 wt% aqueous acetic acid solution: ethanol = 0.5:2:97.5 (weight ratio) was stirred with a stirrer at room temperature for 1 hour to prepare a composition for forming a primer layer. Then, this composition was applied to the surface of the inorganic substrate with a bar coat (#10) as shown in Table 1, and dried in a dryer at 50°C for 5 minutes and then at 120°C for 30 minutes to form a primer layer. After this, an intermediate layer and a surface layer were produced in this order by the same manufacturing method as in Example 1, and a component sample was obtained.

[0130] Example 13 Compound 1 having a betaine structure at 0.3%, anionic monomer 1 at 0.7%, multifunctional acrylate at 30%, polymerization initiator at 0.75%, and surfactant 1 at 0.1%, each in terms of weight concentration, were dissolved in a solvent, stirred with a stirrer for 1 hour, and applied to the substrate with a bar coater (#24). Immediately after application, the mixture was placed in a hot air drying oven and left to stand at 60°C for 10 minutes. Then, an ultraviolet irradiation device (MDB15001N-01, manufactured by SunEnergy Co., Ltd.) was used to irradiate the mixture with an accumulated light dose of 1000 mJ / cm. 2 The coated surface was irradiated with UV light to cure so that the curing temperature reached 100°C (measured with an ultraviolet integrating light meter, C9536-254, manufactured by Hamamatsu Photonics K.K.). To remove any uncured components, the surface was washed with a neutral detergent, rinsed with ion-exchanged water or ultrapure water, and then left to dry at room temperature for at least one hour to obtain a component sample.

[0131] Example 14 Compound 1 having a betaine structure at 0.35%, anionic monomer 3 at 0.15%, multifunctional acrylate at 30%, polymerization initiator at 0.75%, and surfactant 2 at 0.25% by weight were dissolved in a solvent, stirred with a stirrer for 1 hour, and applied to the substrate with a bar coater (#24). Immediately after application, the substrate was placed in a hot air drying oven and allowed to stand at 60°C for 10 minutes. After that, an ultraviolet irradiation device (MDB15001N-01, SunEnergy Co., Ltd.) was used to irradiate the substrate with an accumulated light dose of 1000 mJ / cm. 2 The coated surface was irradiated with UV light to cure so that the curing temperature reached 100°C (measured with an ultraviolet integrating light meter, C9536-254, manufactured by Hamamatsu Photonics K.K.). To remove any uncured components, the surface was washed with a neutral detergent, rinsed with ion-exchanged water or ultrapure water, and then left to dry at room temperature for at least one hour to obtain a component sample.

[0132] Comparative Examples 1 to 3 A member sample was obtained in the same manner as in Example 1, except that only the compound having a betaine structure shown in Table 1 was used as the surface layer-forming composition.

[0133] Comparative Examples 4 and 5 In the production method of Example 1, a member sample was obtained in the same manner except that only the anionic monomers shown in Table 1 were used as the composition for forming the surface layer.

[0134] Comparative Example 6 In the production method of Example 1, as the composition for forming the surface layer, in addition to Compound 1 having a betaine structure and Anionic Monomer 1, Silane Compound 2 (3-methacryloxypropyltrimethoxysilane) was further added, and these were dissolved in a solvent so that their total was 10% by weight concentration. A polymerization initiator was added post-addition at a weight concentration of 0.2% to this solution, and it was stirred with a stirrer for 1 hour to prepare the composition for forming the surface layer. Thereafter, a member sample was obtained by the same production method as in Example 1.

[0135] Comparative Example 7 The acrylic plate as the base material was used as the member sample as it was.

[0136] 3. Evaluation and Results 3-1.XPS evaluation <Preparation of Evaluation Samples> A region of about 1 cm square size was cut from the plate-shaped member sample and used as the measurement sample. Before measurement, the surface of the measurement sample was washed to sufficiently remove the dirt adhering to the surface. Specifically, it was slid and washed with a sponge using a neutral detergent, then ultrasonically washed in ultrapure water at room temperature for 10 minutes, and then thoroughly rinsed with ultrapure water.

[0137] <XPS Measurement> ·XPS Measurement Device K-alpha (manufactured by ThermoFisher Scientific Co., Ltd.) was used. ·XPS Measurement Conditions X-ray Conditions: Monochromatized AlKα ray, 72W - 12KV Photoelectron Extraction Angle: 90° Analysis Region: 400μmφ Neutralization Gun Conditions: 200μA Ion Gun Conditions: 10mA (Survey) Time per step: 10ms Energy step size: 1.000 eV Sweep: 2 times Pass energy: 200 eV Scanning range: -10 to 1350 eV (Narrow) Time per step: 50 ms Energy step size: 0.100 eV Sweep: 5 times Pass energy: 50 eV Scanning range: C1s peak 279.000 eV to 298.000 eV, O1s peak 525.000 eV to 545.000 eV, N1s peak 392.000 eV to 410.000 eV, S2p peak 157.000 eV to 175.000 eV, Si2p peak 95.000 eV to 110.000 eV, P2p peak 124.000 eV to 144.000 eV

[0138] <(Atomic concentrations of S, N, Si, P)> The atomic concentrations of the detected elements were calculated from the obtained spectra using the data analysis software Thermo Avantage (version 5.9916, manufactured by Thermo Fisher Scientific Co., Ltd.). First, using the spectra obtained from the survey analysis, it was confirmed whether the cleaning was properly done. For the spectra obtained from the narrow analysis, after charge correction with the C1s peak set at 284.5 eV, the background was removed by the Smart method for the peaks based on the electron orbits of the measured atoms, and then the peak area intensity was calculated. An analysis process of dividing by the sensitivity coefficient specific to the device preset in the data analysis software was performed to calculate the atomic concentrations when the total of C atoms, O atoms, N atoms, S atoms, Si atoms, and P atoms was 100%. The results are shown in Table 1.

[0139] <Peak separation of N atoms> To separate the peak derived from the +1 valence N atom (N + ) contained in the betaine structure from the peak derived from the other 0 valence N atom (N 0 ), the following method was used. N+ The peak position was fixed at 401.4 to 401.8 eV and the full width at half maximum of the peak was fixed at 1.6 eV. 0 The peak position of was fixed at 398.7 to 399.4 eV and peak fitting was performed. The N + , N 0 The atomic concentrations of each are shown in Table 1.

[0140] The following conditions were used for peak fitting: <Peak fitting conditions> Fitting Algorithm:Powell Maximum Iterations:90 Convergence:1e-05 Gauss-Lorentz Mix:Product

[0141] <Betaine ratio> The S atom concentration, P atom concentration and N atom concentration obtained by the XPS measurement mentioned above + The betaine ratio was calculated from the atomic concentration. + Since the atoms are contained only in the betaine structure, and the S atoms and P atoms are contained in both the betaine structure and the anion structure, the betaine ratio can be calculated as follows: Betaine ratio (%) = 100 × [N + Atomic concentration / (S atom concentration + P atom concentration)] In addition, the analysis depth by XPS is about 10 nm, but in the manufacturing method of the component samples of the examples and comparative examples, a sufficient amount of composition is applied and cured to form a layer thickness of 10 nm, and the layer thickness is sufficiently thicker than the analysis depth by XPS. Therefore, the analysis by XPS can analyze the surface layer components without being affected by the substrate. In addition, the surface to be coated can be covered by coating with spin coating or bar coating, and the substrate is not exposed. As described above, the analysis of the surface layer components can be performed by XPS without being affected by the substrate.

[0142] 3-2.Contact angle The static contact angle of water with respect to the surface of the surface layer was measured under the following measurement conditions using the following device and software. The results are shown in Table 1. Equipment: DMo-702 (Kyowa Interface Science Co., Ltd.) Software: Interface measurement / analysis integrated system FAMAS version: 7.3.0 Measurement method: Droplet method Droplet volume: 2.0μL Waiting time: 1000ms Analysis method: θ / 2 method

[0143] 3-3. Evaluation of water stain removal performance <Creating limescale> 20 μL of tap water (Chigasaki, Kanagawa Prefecture) was dropped onto the surface of each component sample using a micropipette, and the sample was placed in a thermostatic chamber (manufactured by Espec Corporation) and left to stand at 25°C and a relative humidity of 75% for 24 hours to obtain samples with water stains formed.

[0144] <Cleaning evaluation> The obtained samples were evaluated for their ability to clean water stains using the following method. Using a sliding machine (manufactured by Tester Sangyo Co., Ltd.), the sliding load was gradually increased and the surface on which water stains had formed was slid at the following levels. The sample surface was then visually observed, and the level at which the water stains were no longer visible was evaluated as the water stain cleaning ability of that sample. The results are shown in Table 1.

[0145] Level 6: A commercially available urethane sponge (Scotch-Brite Bath Shine, manufactured by 3M Japan Co., Ltd.) is soaked in water and subjected to a load of 25 g / cm 2 ] 5 round trips Level 5: A commercially available urethane sponge (Scotch-Brite Bath Shine, manufactured by 3M Japan Co., Ltd.) is soaked in water and subjected to a load of 50 g / cm 2 ] 5 round trips Level 4: A commercially available urethane sponge (Scotch-Brite Bath Shine, manufactured by 3M Japan Co., Ltd.) was soaked in a mixture of water and neutral detergent (Bath Magiclean, manufactured by Kao Corporation) in a weight ratio of 90:10, and subjected to a load of 25 [g / cm 2 ] 5 round trips Level 3: A commercially available urethane sponge (Scotch-Brite Bath Shine, 3M Japan) was soaked in water and a neutral detergent (Bath Magiclean, Kao Corporation) in the same ratio as in Level 4, and subjected to a load of 50 g / cm 2 ] 5 round trips Level 2: A commercially available urethane sponge (Scotch-Brite Bath Shine, manufactured by 3M Japan Co., Ltd.) was soaked in water and a neutral detergent (Bath Magiclean, manufactured by Kao Corporation) mixed in the same ratio as in Level 4, and subjected to a load of 90 [g / cm 2 ] 25 round trips Level 1: A commercially available urethane sponge (Scotch-Brite Bath Shine, manufactured by 3M Japan Co., Ltd.) was soaked in water and an abrasive cleaner (Kiraria, manufactured by TOTO Co., Ltd.) and subjected to a load of 50 g / cm 2 ] 5 round trips Level 0: Cannot be obtained even at level 1

[0146] 3-4. Protein adsorption evaluation <Preparation of protein-containing suspension> 2.5 g of commercially available wool keratin (manufactured by Tokyo Chemical Industry Co., Ltd.) was mixed and suspended in 100 mL of ion-exchanged water, to which 0.25 g of triolein (manufactured by Kanto Chemical Co., Ltd.) was added in order to increase the dispersibility of the keratin, and ultrasonic treatment was performed for 10 minutes in warm water at 40°C. Then, centrifugation was performed at 15,000 rpm for 10 minutes, and the supernatant was removed. Then, the same amount of ion-exchanged water as the removed supernatant was replenished. Then, ultrasonic treatment was performed for 10 minutes in warm water at 40°C to obtain a suspension.

[0147] <Protein adhesion and cleaning> After immersing the component sample in the above suspension for 10 minutes, the component sample was taken out of the suspension. Then, ultrapure water was applied to the surface of the component sample using a dropper at a concentration of 0.4 [mL / cm 2 ] and washed. The component sample was then tilted at an angle of 25° and dried for one hour. This procedure was repeated twice to obtain a component sample with keratin attached.

[0148] <Observation of the surface of a component sample with proteins attached> Using a laser microscope LEXT OLS5000 (Olympus Corporation), a magnification of 117 times and standard mode (pitch 1.2 μm) were selected, and images of 2580 μm × 2580 μm per field of view were taken. The specifications of the microscope are as follows. Equipment:OLS5000 Product Version: 1.2.1.4807 Light source: 405nm semiconductor laser Detection system: Photomultiplier Objective lens: OLYMPUS MPlan APO N 5X / 0.15 LEXT

[0149] The photographed images are shown in Figures 2 and 3. Figure 2 is an image of the member sample of Example 2, and Figure 3 is an image of the member sample of Comparative Example 5. The black structures seen in the images are attached proteins. The protein attachment area ratio was calculated by the method shown below.

[0150] <Calculation of protein adhesion area ratio> The obtained images were used to calculate the protein adhesion area ratio using the image processing library "OpenCV" (version: 4.5.5). First, the images taken with a laser microscope were imported into the library, and after monochrome image processing, binarization processing was performed. The threshold value for the binarization processing was appropriately adjusted between pixel values ​​of 150 and 160 so that the attached protein would be selected. From this, the total area ratio was calculated. This total area ratio was defined as the protein adhesion area ratio. The results are shown in Table 1.

[0151] 3-5. Evaluation of sliding durability A sliding durability test was carried out on the member sample of Example 3 using a sliding machine (manufactured by Tester Sangyo Co., Ltd.). A commercially available urethane sponge (Scotch-Brite Bath Shine, manufactured by 3M Japan Co., Ltd.) was soaked in a mixture of water and neutral detergent (Bath Magiclean, manufactured by Kao Corporation) in a weight ratio of 90:10, and subjected to a load of 25 [g / cm 2The surface of the sample was reciprocated 5,000 times with the same cloth. The sample was washed with running water, dried, and the static contact angle of water was measured by the method described above. The sliding durability was evaluated according to the following criteria. ○: Static contact angle of water after sliding durability test is 35 degrees or less ×: The static contact angle of water after the sliding durability test is greater than 35 degrees.

[0152] As a result, the static contact angle of water after the sliding durability test in the member sample of Example 3 was 12.0 degrees, and the evaluation was good.

[0153] 3-6. Film thickness evaluation The member sample of Example 3 was cut in the cross-sectional direction. The thickness of the cut portion, including the intermediate layer and the surface layer, was measured using a scanning electron microscope, and found to be 6 μm. The scanning electron microscope used was as follows: Equipment: Regulus8220 (Hitachi High-Tech Corporation) Acceleration voltage: 1 kV Magnification: 6000x

[0154] GCIB-XPS evaluation <Preparing evaluation samples> The measurement sample was a 1 cm square area cut from a plate-shaped component sample. Before the measurement, the surface of the measurement sample was cleaned to thoroughly remove any dirt adhering to the surface. Specifically, the sample was rubbed with a sponge using a neutral detergent, then ultrasonically cleaned in ultrapure water at room temperature for 10 minutes, and then thoroughly rinsed with ultrapure water. ·XPS measurement device The XPS measurement device used was QUANTERA II (manufactured by ULVAC-PHI, Inc.). XPS measurement conditions X-ray conditions: Monochromatic AlKα radiation, 25W-15KV Photoelectron extraction angle: 45° Analysis area: 100μmφ Neutralizer gun requirements: Auto Neutralizer Ion gun conditions: Auto Neutralizer (narrow) Time per step: 50 ms Energy step size: 0.100 eV Sweep: 5 times Pass energy: 55 eV Scanning range: C1s peak 279.000 eV to 299.000 eV, O1s peak 525.000 eV to 545.000 eV, N1s peak 392.000 eV to 410.000 eV, S2p peak 157.000 eV to 177.000 eV, P2p peak 124.000 eV to 144.000 eV · GCIB sputtering conditions The following conditions were used for GCIB sputtering. Beam voltage: 10 kV Beam current: 30 nA

[0155] <Calculation of Si atomic concentration> The atomic concentrations of the detected elements were calculated from the obtained spectra using the data analysis software MultiPaK (version 9.0, manufactured by RBD Instruments Co., Ltd.). For the spectra obtained by XPS measurement, charge correction was performed with the C1s peak set at 284.5 eV. Then, after removing the background from the peaks based on the electron orbits of the measured atoms by the Shirley method, the peak area intensity was calculated, and an analysis process of dividing by the sensitivity coefficient specific to the apparatus preset in the data analysis software was performed to calculate the Si atomic concentration when the total of C atoms, O atoms, N atoms, S atoms, Si atoms, and P atoms was 100%.

[0156] The depth from the surface was calculated by integrating the sputtering time and the sputtering rate. Also, the sputtering rate was calculated by dividing the measured depth obtained by observing the sputtering marks of the sample after measurement with a laser microscope by the sputtering time.

[0157] The Si atomic concentration at a point 1 μm deep from the surface was 0.0% for Example 1 and 1.1% for Comparative Example 6. Also, each sample was polished with waterproof abrasive paper #800 (manufactured by Riken Corundum) under a load of 200 g / cm 2After 20 reciprocations with a brush, the above-mentioned evaluation of water stain cleaning performance was performed. Example 1 was given a cleaning performance level of 5, and Comparative Example 6 was given a cleaning performance level of 0.

[0158] [Table 1] [Explanation of symbols]

[0159] 10. Materials 1 Base material 2 Surface layer 3. Middle tier 4 Primer layer

Claims

1. A member, The member includes a substrate and a surface layer, The surface layer includes a structure represented by the following formula (A1) and a structure represented by the following formula (A2), 【Chemistry 1】 【Chemistry 2】 In formula (A1), L 1 is -COO-, -CONH-, -(CH 2 ) m - (where m is a natural number), R 1 is H or CH 3 and X 1 is a functional group represented by the following formula (B) or the following formula (C), 【Chemistry 3】 【Chemistry 4】 In formula (B), R 3 and R 6 Each independently represents -(CH 2 ) l - (l is a natural number from 1 to 10), R 4 and R 5 each independently represents an organic group containing C and H as essential components and O as an optional component, and not containing N or S, In formula (C), R 7 and R 8 Each independently represents -(CH 2 ) l - (l is a natural number from 1 to 10), R 9 , R 10 , R 11 each independently represents an organic group containing C and H as essential components and O as an optional component, and not containing N or S, In formula (A2), L 2 is -COO-, -CONH-, -(CH 2 ) m -(m is a natural number), -Ph-, R 2 is H or CH 3 and X 2 is a functional group represented by the following formula (D) or formula (E): 【Chemistry 5】 【Chemistry 6】 In formula (E), R 12 is an organic group containing C and H as essential components and O as an optional component, and not containing N or S, the concentration of Si atoms obtained by measuring the surface of the member by X-ray photoelectron spectroscopy (XPS) is 1.0% or less; The component is characterized in that it is used in an environment in which water and contaminants containing organic and inorganic components adhere to the surface, and the water dries while leaving the water and contaminants mixed on the surface, a cycle of which is repeated.

2. 2. The member according to claim 1, wherein a concentration of Si atoms obtained by measuring a region from the surface of the member to a depth of 1 μm by X-ray photoelectron spectroscopy (XPS) is 1.0% or less.

3. 2. The member according to claim 1, wherein the concentration of S atoms, the concentration of P atoms, or the sum of the concentration of S atoms and the concentration of P atoms, obtained by measuring the surface of the member by X-ray photoelectron spectroscopy (XPS), is 0.6% or more.

4. 3. The member according to claim 2, wherein the concentration of S atoms, the concentration of P atoms, or the sum of the concentration of S atoms and the concentration of P atoms, obtained by measuring the surface of the member by X-ray photoelectron spectroscopy (XPS), is 0.6% or more.

5. The surface of the member is measured by X-ray photoelectron spectroscopy (XPS) to obtain N + 2. The component of claim 1, wherein the concentration of atoms is 0.3% or greater.

6. The surface of the member is measured by X-ray photoelectron spectroscopy (XPS) to obtain N + 3. The member of claim 2, wherein the concentration of atoms is 0.3% or greater.

7. The surface of the member is measured by X-ray photoelectron spectroscopy (XPS) to obtain N + 4. The member of claim 3, wherein the concentration of atoms is 0.3% or greater.

8. The surface of the member is measured by X-ray photoelectron spectroscopy (XPS) to obtain N + 5. The member of claim 4, wherein the concentration of atoms is 0.3% or more.

9. The surface of the member is measured by X-ray photoelectron spectroscopy (XPS) to obtain N + The member according to any one of claims 1 to 8, wherein the betaine ratio calculated from the concentration of the S atom, the concentration of the P atom, and the concentration of the S atom by the following formula is 16% or more and 55% or less. Betaine ratio (%) = 100 x [N + atom concentration / (S atom concentration+P atom concentration)]

10. The member according to any one of claims 1 to 8, wherein the surface layer comprises a random copolymer of the structure represented by formula (A1) and the structure represented by formula (A2).

11. The member according to claim 9 , wherein the surface layer comprises a random copolymer of the structure represented by formula (A1) and the structure represented by formula (A2).

Citation Information

Patent Citations

  • Composition for forming hydrophilic membrane and hydrophilic member

    JP2008239949A

  • Hydrophilic resin composition and laminated sheet

    WO2018079592A1

  • Hydrophilic structure and production method for hydrophilic structure

    WO2018155577A1